NEW TECHNOLOGIES AND THE CURRENT COMMUNICATIONS MODEL IN THE 2018 BRAZILIAN ELECTIONS - Lôbo, Edilene; Morais, José Luiz Bolzan de (Novos Estudos Jurídicos, 2019)
This article considers the impact of new technologies in the 2018 Brazilian elections, and investigates the possibilities of changes due to the prominent use of social networks to directly connect citizens and candidates, without the customary intervention of political parties and traditional media. It also questions the role of fake news in the electoral process, and the means to fight it, without undermining free thought, as an essential human right for the practice of citizenship in the new digital age.